2020
DOI: 10.3389/fnins.2020.611393
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Cerebrospinal Fluid Glycerophospholipids and Sphingolipids in Cognitively Healthy Participants With Alzheimer’s Biomarkers Precedes Lipolysis in the Dementia Stage

Abstract: Insight into lipids’ roles in Alzheimer’s disease (AD) pathophysiology is limited because brain membrane lipids have not been characterized in cognitively healthy (CH) individuals. Since age is a significant risk factor of AD, we hypothesize that aging renders the amyloid precursor protein (APP) more susceptible to abnormal processing because of deteriorating membrane lipids. To reflect brain membranes, we studied their lipid components in cerebrospinal fluid (CSF) and brain-derived CSF nanoparticle membranes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Conversely, levels of ceramides, specifically monohexosylceramides, were found to be elevated in PD patients with GBA mutations. Accordingly, higher ceramide levels have been observed in the plasma, primary visual cortex, and CSF of PD patients [168,[173][174][175]. This trend has also been observed in mice models of Lrrk2 and PINK1 [176,177].…”
Section: Sphingolipid-induced α-Syn Abnormalities In Pdmentioning
confidence: 61%
See 1 more Smart Citation
“…Conversely, levels of ceramides, specifically monohexosylceramides, were found to be elevated in PD patients with GBA mutations. Accordingly, higher ceramide levels have been observed in the plasma, primary visual cortex, and CSF of PD patients [168,[173][174][175]. This trend has also been observed in mice models of Lrrk2 and PINK1 [176,177].…”
Section: Sphingolipid-induced α-Syn Abnormalities In Pdmentioning
confidence: 61%
“…Elevated levels of SM and cerebrosides have been observed in substantia nigra of male PD patients [179]. Interestingly, SM was also observed to be lower in the ACC of PD [168] patients and the CSF of AD patients [174]. SM treatment of SK-N-SH neuronal cells increased the expression of α-syn.…”
Section: Sphingolipid-induced α-Syn Abnormalities In Pdmentioning
confidence: 94%
“…Despite these efforts, current therapies for AD can only temporarily improve symptoms of memory loss without delaying the course of the disease—i.e., the death of neurons and the decline in higher cognitive functions [ 51 ]. Growing evidence demonstrates that defects in lipid metabolism and, consequently, alterations in vesicular dynamics and synaptic plasticity are related to the pathogenesis of AD [ 4 , 5 ]. Recently, it has been demonstrated that the plasma lipidome is dysregulated in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a neurodegenerative disorder among the elderly, characterized by progressive deterioration of cognition, with a complex etiology involving multiple processes [ 1 ] Neuropathological features include senile plaques (SP) composed of aggregated amyloid β peptides (Aβ) derived from aberrant processing of the amyloid precursor protein (APP), neurofibrillary tangles (NFT) composed of hyperphosphorylated tau protein, and synaptic and neuronal loss [ 2 ]. In light of many recent studies, defects in lipid metabolism and consequent alterations in the membrane concentration of phospholipids may impact the development of pathophysiological features of AD [ 3 , 4 , 5 , 6 , 7 , 8 ]. In fact, the formation of SP and NFT correlates with decreased phospholipid biosynthesis and increased lipid degradation or peroxidation [ 9 , 10 ] that contribute to synaptic impairment and neuronal loss [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathological features include senile plaques (SP), composed of aggregated amyloid β peptides (Aβ) derived from aberrant processing of the amyloid precursor protein (APP), neuro brillary tangles (NFT), composed of hyperphosphorylated tau protein, and synaptic and neuronal loss [2]. In light of many recent studies, defects in lipid metabolism and consequent alterations in the membrane concentration of phospholipids may impact the development of pathophysiological features of AD [3][4][5][6][7][8]. In fact, the formation of SP and NFT correlates with decreased phospholipid biosynthesis and increased lipid degradation or peroxidation [9,10] that contribute to synaptic impairment and neuronal loss [11].…”
Section: Introductionmentioning
confidence: 99%